2023
DOI: 10.1039/d2tc04481a
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional lead-free perovskite single crystals with high X-ray response grown by liquid phase diffusion

Abstract: Organic-inorganic hybrid bismuth halides, as an essential member of the lead-free family, are highly expected since they share a similar electronic configuration with lead analogs. However, the growth of bismuth-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We note that four anions were arranged as terminals and the other two served as a bridge between two neighboring BiBr 6 octahedrons, inferring the corner shared packing 1D zigzag chain-type arrangements separated by the respective organic ligand cations. This structural order is comparable to the previous work by Zhang et al, Ji et al, and other work. ,, …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We note that four anions were arranged as terminals and the other two served as a bridge between two neighboring BiBr 6 octahedrons, inferring the corner shared packing 1D zigzag chain-type arrangements separated by the respective organic ligand cations. This structural order is comparable to the previous work by Zhang et al, Ji et al, and other work. ,, …”
Section: Resultssupporting
confidence: 92%
“…This structural order is comparable to the previous work by Zhang et al, 53 Ji et al, 54 and other work. 6,55,56 The vibrational features in all hybrid perovskites have been examined using Fourier transform infrared spectroscopy and Raman spectroscopy. As shown in Figure 3a, all hybrid perovskites exhibit several sharp peaks at wavenumbers of 4000−500 cm −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This fact is also confirmed by the sensitivity calculation of 1 and 2, that 201 and 114 μC Gy air −1 cm −2 , respectively (Note S2). 44,45 In addition, 1 showed no significant drift of the dark current in the test of continuously switching X-ray dose rate, indicating that it has good photoresponse characteristics (Figure 5e). The stability of the photoelectric switch was characterized by a constant radiation dose rate of 13.22 μGy air s −1 .…”
Section: ■ Introductionmentioning
confidence: 95%
“…Along with the development of nontoxic perovskites and their derivatives, metal hybrid halides had the potential to be used in light emission diodes (LEDs) owing to their high photoluminescence quantum yields (PLQYs), broad-band emission, and long decay times. Specifically, low-dimensional hybrid halides exhibit excellent photoluminescence properties with potential applications in X-ray scintillation. , Especially, Cu + -, Sb 3+ -, and Mn 2+ -based zero-dimensional (0D) halides have been designed as potential candidates for highly efficient and environmentally friendly scintillators due to their excellent light yield and high-energy radiation absorption performance. For instance, Xia et al reported a Mn 2+ -doped Cs 2 ZnBr 4 crystal with excellent scintillation performance, whose light yield reached about 15,600 photons MeV –1 and the detection limit was as low as 1.16 μGy air s –1 .…”
Section: Introductionmentioning
confidence: 99%